Prenatal stress unmasks behavioral phenotypes in genetic mouse models of neurodevelopmental disorders - Harper, Kathryn M.; Harp, Samuel J.; Moy, Sheryl S. (Frontiers in Behavioral Neuroscience, 2023)
Neurodevelopmental disorders (NDDs) are complex conditions characterized by heterogeneous clinical profiles and symptoms that arise in infancy and childhood. NDDs are often attributed to a complicated interaction between genetic risk and environmental factors, suggesting a need for preclinical models reflecting the combined impact of heritable susceptibility and environmental effects. A notable advantage of “two-hit” models is the power to reveal underlying vulnerability that may not be detected in studies employing only genetic or environmental alterations. In this review, we summarize existing literature that investigates detrimental interactions between prenatal stress (PNS) and genes associated with NDDs, with a focus on behavioral phenotyping approaches in mouse models. A challenge in determining the overall role of PNS exposure in genetic models is the diversity of approaches for inducing stress, variability in developmental timepoints for exposure, and differences in phenotyping regimens across laboratories. Identification of optimal stress protocols and critical windows for developmental effects would greatly improve the use of PNS in gene x environment mouse models of NDD.